A Feasibility Study of Percutaneous Peripheral Nerve Stimulation for the Treatment of Postoperative Pain Following Total Knee Arthroplasty. Issue 5 (19th July 2018) - Ilfeld, Brian M.; Ball, Scott T.; Gabriel, Rodney A.; Sztain, Jacklynn F.; Monahan, Amanda M.; Abramson, Wendy B.; Khatibi, Bahareh; Said, Engy T.; Parekh, Jesal; Grant, Stuart A.; Wongsarnpigoon, Amorn; Boggs, Joseph W.
Abstract : Introduction: The objective of the present feasibility study was to investigate the use of a new treatment modality—percutaneous peripheral nerve stimulation (PNS)—in controlling the often severe and long‐lasting pain following total knee arthroplasty (TKA). Methods: For patients undergoing a primary, unilateral TKA, both femoral and sciatic open‐coil percutaneous leads (SPR Therapeutics, Cleveland, OH) were placed up to seven days prior to surgery using ultrasound guidance. The leads were connected to external stimulators and used both at home and in the hospital for up to six weeks total. Results: In six of seven subjects (86%), the average of daily pain scores across the first two weeks was <4 on the 0–10 Numeric Rating Scale for pain. A majority of subjects (four out of seven; 57%) had ceased opioid use within the first week (median time to opioid cessation for all subjects was six days). Gross sensory/motor function was maintained during stimulation, enabling stimulation during physical therapy and activities of daily living. At 12 weeks following surgery, six of seven subjects had improved by >10% on the Six‐Minute Walk Test compared to preoperative levels, and WOMAC scores improved by an average of 85% compared to before surgery. No falls, motor block, or lead infections were reported. Conclusions: This feasibility study suggests that for TKA, ultrasound‐guided percutaneous PNS is feasible in the immediate perioperative period and may provide analgesia without the undesirable systemic effects of opioids or quadriceps weakness induced by local anesthetics‐based peripheral nerve blocks.